Some methods of fish capture in Mercedes waters, Camarines Norte - Cayman, Dionisio M. (College of Fisheries, University of the Philippines, 1953)
The Filipinos like other people, in the Indi Pacific Region depend mostly on fish for their supply of animal protein for their normal growth and development. It is a sad fact however, that with our ever-increasing population there is practically no corresponding increase in fish supply. Therefore, something must be done to remedy the situation. Above all is a sound management of our fishing grounds and conservation of our natural resources which every Filipinos and every one who enjoys the benefit of the Philippines Government should observed strictly all existing laws and rules governing it. As means of gradually affecting the increase of the production of fish products to provide the people specially the common mass with their vital needs. Fishermen have been employing and modernized form of fishing gear. On the following pages are described some effective fishing gear operated in Camarines Norte, one of the most important fishing grounds in the Philippines. It is expose during Northeast Monsoon as that fishing steps that period, thus giving chance for the fishes to grow. Fishing can be carried on throughout the year in some parts of the Bay.